Glutamine metabolism in the proliferation of GS-expression pituitary tumor cells. Issue 3 (March 2020) - Hu, Jintao; Chen, Qingbo; Ding, Xiao; Zheng, Xin; Tang, Xuefeng; Li, Song; Yang, Hui
Abstract : Objective: Many cancer cells cannot survive without exogenous glutamine (Gln); however, cancer cells expressing glutamine synthetase (GS) do not have this restriction. Previous metabolomics studies have indicated that glutamine metabolism is altered during pituitary tumorigenesis. However, the main role of Gln in pituitary adenoma (PA) pathophysiology remains unknown. The aim of this study was to evaluate the expression of GS and the main role of Gln in human PAs. Methods: We used cell proliferation assay and flow cytometry to assess the effect of Gln depletion on three different pituitary cell lines and human primary PA cells. We then investigated the expression level of Gln synthetase (GS) in 24 human PA samples. At last, we used LC-MS/MS to identify the differences in metabolites of PA cells after the blockage of both endogenous and exogenous Gln. Results: PA cell lines showed different sensitivities to Gln starvation, and the sensitivity is correlated with GS expression level. GS expressed in 21 out of the 24 human PA samples. Furthermore, a positive p53 and ki-67 index was correlated with a higher GS expression level ( P < 0.05). Removal of both endogenous and exogenous Gln from GS-expressing PA cells resulted in blockage of nucleotide metabolism and cell cycle arrest. Conclusions: Our data indicate that GS is needed for PA cells to undergo proliferation during Gln deprivation, and most human PA cells express GS and might have a negative response to exogenous Gln depletion. Moreover, Gln is mainly responsible for nucleotide metabolism in the proliferation of GS-expressing pituitary tumor cells.